Contemporary Issues in Land Use Planning - Appiah-Opoku, Seth (Sustainable Development, 2023)
Land use planning is a complex task that affects all aspects of life in contemporary societies. As such, this book includes contributions from specialists around the globe who have successfully undertaken empirical studies and analysis of rural and urban planning problems. Based on empirical research, this book discusses a variety of topics including agricultural land preservation plans and laws in Iran; using a multi-objective land allocation model to simulate urban growth in the Sarakh border city of Iran; implementation and management of urban land use plans in Ghana; spatiotemporal analysis of urban expansion methods for land use planning; and linking land use changes to policy decisions in Iran. Although limited in scope, the book serves as important reference material on similar contemporary land use planning issues in the developing world.